The influence of gender and self-esteem on attitudes of Nigerians towards foreign and made in Nigeria products (2000)
The study investigated the influence of gender and self-esteem on the attitude of Nigerians towards foreign and made in Nigeria products .One hundred and fifty randomly drawn respondents from the Faculty of Business Administration, University of Lagos Student population were involved in the study. The respondents were made up of 86 males (representing 57.3%) and 64 females (representing 47.7%). Their age ranged from 18 - 30) years. The mean age was 21.19 with a standard deviation of 5.39. Four hypotheses were tested using analyses of variance and Pearson correlation statistics. Attitude towa.rds foreign and made in Nigeria products was measured using Ajzen & Fishbein’s (1980) thirty-one item attitude questionnaire which was modified and revalidated by the authors. Self-esteem was measured using Adaranijo and Oyefeso’s (1986) self-esteem scale. The result of the first hypothesis revealed that consumers' gender had no significant effect on Nigerians' altitude towards foreign and made in Nigeria products. In hypothesis two, if was revealed that consumers' self-esteem had a significant effect on foreign made products F (1. 146) = 4.14: P < 0.05. Similarly, findings of hypothesis three showed that consumers' sex and self-esteem had significant joint effect on consumers' attitude towards foreign and made in Nigeria products. Lastly, results indicated that there was significant positive relationship between participants' attitude towards foreign products and participants' attitude towards Nigerian products. The implication of findings was that marketers should as a matter of necessity continually research into customers' attitudes towards their products. Discussion of the study's findings was based on the centrality and dynamism of attitudes in marketing research. Recommendations and suggestions were, on the basis of the research’s findings, also made.